Climate change disclosure and financial performance of quoted oil & gas firms in Nigeria - Agbo, Emmanuel; Egbunike, Chinedu Francis (goodwood publishing, 2024)
Purpose: Prior research has demonstrated the critical role that climate change disclosure plays in solving global sustainability challenges connected to human existence and the long-term viability of businesses. The goal of this study is to add to the existing literature on the impact of climate change-related disclosure on the financial performance of oil and gas companies in Nigeria. Research Methodology: The study adopted an ex post facto research design, and the final sample consisted of eight oil and gas companies listed on the NGX for the year 2012-2021. The final sample consisted of a balanced panel of 80 firm-year observations. The dependent variable was Return on Assets (ROA). Data were analyzed using a multiple regression model. Results: The findings showed a positive relationship between CCRD and ROA, which was also confirmed to be significant at the 5% significance level. Limitations: The model includes leverage, audit quality, and firm size, in addition to CCRD, to account for their effect on ROA. Therefore, other factors that may affect firm performance are not included in the model. Contribution: This study addresses one of the most important but less explored issues of environmental research in one of the largest economies in SSA. The data collected from the content analysis are original and provide important evidence of the impact of CCRD on firm performance. These findings encourage oil and gas companies to reduce their carbon emissions and disclose their carbon management activities.